Pemanfaatan Langsung Tanaman Kayu Apu Dadak (Azolla pinnata) Sebagai Pakan Tambahan pada Budidaya Ikan Nila (Oreochromis niloticus) - Ni Putu Sandhitya Candra Kartina; Pande Gde Sasmita Julyantoro; Ni Putu Putri Wijayanti (Environmental Research Center (PPLH) of Udayana University, 2023)
Tilapia is a type of fish favored by freshwater fish consumers because it is easy to cultivate. The problem faced in freshwater fish farming activities is the high price of artificial feed. To deal with these problems, alternative feeds are needed to reduce the use of artificial feeds such as sudden apu wood (Azolla pinnata). This study aims to determine the effectiveness of the sudden apu wood (Azolla pinnata) on the growth and survival of tilapia (Oreochromis niloticus) and to help fish farmers reduce the use of artificial feed. The research method used is an experimental approach method. The experimental design in this study was a Randomized Block Design (RAK) which consisted of 3 treatments with 3 replications. Treatment A (direct feeding of 100% Azolla pinnata plants), Treatment B (direct feeding of 50% Azolla pinnata plants and 50% pellets), and Treatment C (100% pellet feeding). The results showed the absolute weight growth of treatment A 12.18±5.66 g, treatment B 17.73±4.40 g, treatment C 24.53±3.80 g. The absolute length growth of treatment A was 2.22 ± 0.60 cm, treatment B 2.54 ± 0.40 cm, treatment C 3.50 ± 0.37 cm. The survival rate of treatment A was 66.67±11.54%, treatment B and treatment C were 100±0%. Feed conversion ratio (FCR) for treatment A 4.8±2.28, treatment B 2.1±0.45, treatment C 1.7±0.17. The water quality of the three feeding treatments had no significant effect on pond water quality and was still within the optimal range for tilapia growth and cultivation.